A clearer sense of self: relationship between bilingualism and overconfidence bias. Issue 7 (9th August 2022) - Li, Heng; Shen, Shu
ABSTRACT: Because of the quickening pace of globalisation, recent years have witnessed a rise of bilingualism throughout the world. Prior research has documented a range of cognitive benefits and costs of being bilingual. The current work uncovers another potential positive side of being bilingual: the control of overconfidence in peer-comparison problems. Based on previous findings that bilingualism is positively related to enhanced cognitive functions, we predict that individuals' overconfidence will be negatively correlated with their bilingual experience and this relationship will be independent of crosscultural learning and of the modality of the bilingual experience. In line with our theoretical perspective, significant negative associations emerged between L2 proficiency and overconfidence scores in both Chinese speaking learners of English and English-speaking learners of Chinese (Studies 1–3). These results suggest that the inverse relationship between bilingualism and overconfidence cannot be accounted for by the effects of acculturation. Additionally, such associations were also observed in Chinese-Chinese Sign Language bimodal bilinguals (Study 4). The robust findings across different cultures and modalities suggest that as individuals learn to master two languages, the bilingual experience may reduce their overconfidence bias and nudge them to make more rational judgment and decision-making in comparison to monolingual groups.